Porous membranes of montmorillonite/poly(vinylidene fluoride-trifluorethylene) for Li-ion battery separators - Lanceros-Méndez, S. (2012)
Porous membranes of poly(vinylidene fluoride-trifluoroethylene) with different contents of montmorillonite (MMT) particles were prepared. The filler content does not affect porous morphology but leads to an increase in the average pore size, porosity and electrolyte uptake up to 16 μm, 85% and 325%, respectively, for membrane with 16 wt % of MMT particles. The mechanical properties, ionic conductivity and its temperature stability are improved by the presence of clays. The electrochemical stability reveals a stable window of operation up to 5 V. The overall characteristics of the membranes for battery separators are optimized for the 4% wt MMT filler content.